The Concept of the Learner in the Perspective of Islamic Education: An In-depth Analysis of Children's Emotional and Spiritual Development - Saiful (International Journal Education and Computer Studies (IJECS), 2023)
- This research explores children's emotional and spiritual development in the context of Islamic education, with a focus on the role of family, school, and society. The concept of the student subject in Islam is explained as the process of forming natural potential, especially in the spiritual and emotional aspects, which is the basis for mature life. The family, as an initial educational institution, has the main responsibility in directing children's development in accordance with religious values. Islamic education is identified as a key factor in shaping the moral, social, and religious dimensions of students. This research uses a descriptive approach by collecting data through library research, analyzing human development theory, and examining the concept of Islamic education. The research results highlight the importance of education in aqidah, worship and morals as the main components in forming a child's personality. The integration of emotional and spiritual development theories in the three educational centers creates individuals who are competent in science, faith, charity, and morality, and can make positive contributions to society.